2022
DOI: 10.3389/fgene.2022.848747
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Signature Based on Necroptosis-Related Genes for Prognosis of Patients With Pancreatic Cancer

Abstract: Pancreatic cancer (PCa) is a highly lethal and aggressive disease, characterized by high mortality rates. Although necroptosis plays a vital role in tumor progression, cancer metastasis, prognosis of cancer patients, necroptosis-related gene (NRG) sets have rarely been analyzed in PCa. Therefore, definition of novel necroptosis-related prognostic markers for PCa patients is urgently needed. Here, we screened 159 NRGs and identified 132 differentially expressed NRGs in The Cancer Genome Atlas (TCGA) and Genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Gene signatures based on copper metabolism-related genes have been reported in a variety of tumor diseases, and prognostic models based on several biological functions have also been widely used in pancreatic cancer [4,[23][24][25][26]. We established a risk score to predict the prognosis of pancreatic cancer based on fve cuproptosis-related lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Gene signatures based on copper metabolism-related genes have been reported in a variety of tumor diseases, and prognostic models based on several biological functions have also been widely used in pancreatic cancer [4,[23][24][25][26]. We established a risk score to predict the prognosis of pancreatic cancer based on fve cuproptosis-related lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al constructed a prognostic signature associated with necroptosis in pancreatic cancer by differential expression analysis and regression analysis, in which patients with risk scores may be correlated with chemotherapy sensitivity (34). Shi et al found that GLUD1, SPATA2, H2AC8, PYGL and TNFS10 among the genes related to necroptosis may be closely related to the prognosis of pancreatic cancer patients, and may be potentially Frontiers in Immunology frontiersin.org related to the activation of PI3K/AKT pathway (35). In contrast, our study is the first analysis of necroptosis associated genes in pancreatic cancer combined with a single cell sequencing dataset.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, necroptosis provides a favorable environment for tumor proliferation and metastasis [ 6 ]. Nowadays, necroptosis-related signatures have been built in several types of cancer [ 8 , 19 , 20 ]. Our study mainly investigated whether NAGs are correlated with the prognosis of GC and whether they could predict patient responses to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%